Analisis Ketahanan Hidup Bayi Neonatal Pada Ibu Berusia Berisiko Di Indonesia 2017 - Novalianisa Permata Sari; Yaya Setiadi (Seminar Nasional Official Statistics, 2022)
In developing countries, including Indonesia, health is still a problem in development that must be resolved, one of which is infant mortality. In 2018, 2.5 million babies in the world experienced neonatal deaths. Babies born to mothers who are younger or older than 20-35 years are at increased risk for neonatal death. The data used in this study is secondary data sourced from the 2017 IDHS. The data were analyzed using descriptive analysis to find out the general description and characteristics of neonatal mortality in women aged at risk and inferential analysis using the survival analysis method with Proportional Hazard model to determine the variables that significantly affect Neonatal infant survival in mothers aged at risk. The results of the analysis was found that the variables that significantly affected the survival of neonatal infants in mothers aged at risk in Indonesia in 2017 were the baby's birth weight, early initiation of breastfeeding, antenatal check-ups, sex of the baby, type of birth, and pregnancy complications.